Pengaruh Branding Terhadap Keputusan Pembelian Konsumen: Studi Empiris Pada Penjualan Gamis Nibras di Nibras House Tuban - Yuliartin, Fenti; Septia Handayani, Ninok; Fakhril Ulum, Mohammad (Jurnal Perbankan Syariah, 2024)
The research aim to determine the influence of branding on the purchase decision of Nibras clothing from Nibras House Tuban. This research is a quantitative study whose sample is 50 people including all people who can be sampled in Tuban City. Using Likert scale questionnaires in surveys to collect data. Using a series of descriptive tests of analysis supported by validity and reliability tests, and hypothesis tests from the F test, T-test and coefficient of determination test using SPSS software version 24. The results of this study show that branding can affect the purchase of Nibras clothes at Rumah Nibras Tuban City.